Multiple sclerosis iron rim lesions are linked to impaired cervical spinal cord integrity using the T1/T2-weighted ratio: clinical investigative study - Wenzel, Nicolas; Wittayer, Matthias Sebastian; Weber, Claudia Ellen; Platten, Michael; Gass, Achim; Eisele, Philipp (Journal of neuroimaging, 2023)
Background and Purpose In multiple sclerosis (MS), iron rim lesions (IRLs) are characterized by pronounced tissue matrix damage. The T1/T2-weighted (T1/T2w) ratio represents a postprocessing MRI approach to investigate tissue integrity, but studies investigating spinal cord pathology are missing until now. The aim of this study was to characterize tissue integrity using the T1/T2w ratio in lesions and the normal-appearing white and gray matter (NAWM, NAGM) in the spinal cord and brain in MS patients with and without brain IRLs. Methods Forty MS patients (20 patients with at least one brain IRL and 20 age- and sex-matched patients without IRLs) were included. Normalized cross-sectional area (nCSA) of the upper cervical cord was calculated in addition to T1/T2w values and standard brain and spinal cord MRI parameters. Results Patients with IRLs had higher disability scores, a smaller nCSA, and a higher cervical T2 lesion volume. T1/T2w values of brain IRLs were significantly lower compared to non-IRLs (p < .001). Furthermore, T1/T2w values of lesions were significantly lower compared to the NAGM and NAWM, both in the brain and the spinal cord (p < .05 for all comparisons). T1/T2w values of the NAGM and NAWM in the brain and spinal cord did not statistically differ between the IRL group and the non-IRL group. Conclusion IRLs constitute an imaging marker of disease severity. T1/T2w ratio maps represent an interesting technique to capture diffuse tissue properties. Calculation of T1/T2w ratio maps of the spinal cord might provide additional insights into the pathophysiological processes of MS.
Erstmals veröffentlicht: 12. Dezember 2022
Gesehen am 06.08.2024